"After the Dust Settles": Foucauldian Narratives of Retired Athletes' "Re-orientation" to Exercise - Luke Jones; Zoe Avner; Jim Denison (Frontiers Media S.A., 2022)
One aspect of sports retirement that has been overlooked until recently is the manner in which retired athletes relate to, and seek to redefine, the meaning of exercise in their post-sport lives. In this article, three Foucauldian scholars present and analyze a series of vignettes concerning their own sense-making and meaning-making about exercise following their long-term involvement in high-performance soccer (authors one and two) and distance running (author three). In doing so, this paper aims to underline the problematic legacy of high-performance sport for retiring athletes' relationship to movement and exercise, and to highlight how social theory, and Foucauldian theorization in particular, can serve to open new spaces and possibilities for thinking about sports retirement.